THE ROLE OF THE STATE MECHANISM IN BUILDING A MODERN LEGAL STATE - Aminov Dalerjon Alisher-oglu (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. In this article, the essence of the concept of the state mechanism, the theoretical analyzes put forward by national scientists in this regard, its organization, operation, in particular, the principle of separation of powers, the historical formation process of the state mechanism, as well as its main participants and shortcomings and problems in the process of operation are discussed. After studying it, a detailed opinion is given about making proposals for their elimination.